1985
DOI: 10.1093/geronj/40.6.657
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Influences on Aging of Fischer 344 Rats: I. Physical, Metabolic, and Longevity Characteristics

Abstract: The aims of this research were (a) to compare food restriction initiated in adult life of male Fischer 344 rats with that limited to early life or involving most of the life span on physical, metabolic, and longevity characteristics and (b) to study a similar level of protein restriction without caloric restriction on these characteristics. Food restriction (60% of the ad libitum intake) initiated at 6 months of age markedly increased life span as did a similar restriction started at 6 weeks of age, but food r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
247
2
2

Year Published

1989
1989
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 561 publications
(269 citation statements)
references
References 0 publications
18
247
2
2
Order By: Relevance
“…The 12AL group was used as the control. We initiated CR at 20 weeks; this was performed to avoid any effect of CR on development while retaining effectiveness of increasing lifespan (Yu et al ., 1985). Mice were fed CR (or AL) diets for 12 weeks, before being sacrificed at 32 weeks of age.…”
Section: Methodsmentioning
confidence: 99%
“…The 12AL group was used as the control. We initiated CR at 20 weeks; this was performed to avoid any effect of CR on development while retaining effectiveness of increasing lifespan (Yu et al ., 1985). Mice were fed CR (or AL) diets for 12 weeks, before being sacrificed at 32 weeks of age.…”
Section: Methodsmentioning
confidence: 99%
“…If a single cause of senescence, such as free radicals generated by mitochondria, exists, then all these life-extending manipulations may have one mechanism in common. To determine if there is a single pathway by which senescence is retarded, we have examined four separate manipulations that have been shown to increase lifespan in C. elegans: dietary restriction (DR), cold-/hypothermic-induced longevity (CHIL), decreased insulin signaling, and mutations influencing mitochondrial respiration (Ball et al 1947;Conti et alDietary restriction has been shown to extend lifespan by up to 50% in mammals (Davis et al 1983;Yu et al 1985;Weindruch and Walford 1982). In several different worm models of dietary restriction, evidence has revealed that DAF-16, a forkhead box O (FOXO) transcription factor that is required for lifeextension via the insulin pathway, is not required for the life-extending effects of dietary restriction (Houthoofd et al 2003;Lakowski and Hekimi 1998).…”
Section: Introductionmentioning
confidence: 99%
“…All rats were fed adlibitum until 6 weeks of age, at which time they were separated into two groups: ad libitum-fed (AL) control and diet-restricted (DR) group, whose food intake was restricted of 60% of the food intake of control. Detailed maintenance of animals and dietary procedures are published previously (23).…”
Section: Animals and Dietary Regimen: Specific Pathogen-freementioning
confidence: 99%